Nazir, Muhammad Saqib - (:unkn) unknown (My University, 2026)
My research interests include AI-based nonlinear adaptive control, power converters, renewable energy, distributed energy resources, hybrid energy storage systems, hybrid electric vehicles, smart grid, wireless sensor networks, and supervisory control and data acquisition.